A Remark on Condensation of Singularities - Hardtke, J.-D. (Журнал математической физики, анализа, геометрии, 2013)
Recently Alan D. Sokal in Amer. Math. Monthly 118 (2011), No. 5, 450-452, gave a very short and completely elementary proof of the uniform boundedness principle. The aim of this note is to point out that by using a similar technique one can give a short and simple proof of a stronger statement, namely a principle of condensation of singularities for certain double-sequences of non-linear operators on quasi-Banach spaces, which is a bit more general than a result of I. S. Gál from Duke Math. J. 20 (1953), No. 1, 27-35. Не так давно Алан Д. Сокал в Amer. Math. Monthly 118 (2011), No. 5, 450-452 представил очень короткое и простое доказательство принципа равномерной ограниченности. Цель настоящей заметки - показать, что, используя подобную технику, можно дать короткое и простое доказательство для более сильного утверждения, а именно принципа сгущения сингулярностей для определенных двойных последовательностей нелинейных операторов на квазибанаховых пространствах, которое является немного более общим, чем результат И.С. Гала из Duke Math. J. 20 (1953), No. 1, 27-35.